Islamic and Conventional Perspectives in Islamic Economics and Monetary Economic Equilibrium - Azza Nuha Nisrina; Salisa Khoirun Salsabila; Mohammad Fauzi; Syarifudin Hidayatullah (Penerbit Hellow Pustaka, 2025)
An economic system based on Islamic teachings and sharia principles is known as sharia economics. The goal of sharia economics is to maximize human welfare in a manner consistent with Islamic principles. In developing sharia economics, it is necessary to pay attention to the differences between Islamic and conventional perspectives in economics. The Islamic perspective in sharia economics and economic balance are influential concepts in describing the economic system that is in accordance with Islamic rules and values. Islamic economics uses methods that are closely related to the law of Allah, are based on divinity, and strive for the goals of Allah. Islam concludes that, in economics, income must be spent in accordance with Islamic principles, which include usury, zakat, and scarcity (al-nudrat). In the era of globalization, many opportunities and challenges arise in the economic sector, so it is necessary to develop sharia economics to face these challenges. The Islamic economic system distinguishes between the discussion of the production of goods and services included in the economic system and the discussion of how to obtain, utilize, and distribute goods and services included in its discussion. Unlike other economic systems that do not have a final goal in Allah, sharia economics has a final goal in Allah. The framework of Islamic and conventional economics is fundamentally different. If traditional economics views science as something secular, then Islamic economics is based on religious ideas. The Islamic economic system distinguishes between the discussion of the production of goods and services included in the economic system and the discussion of how to obtain, utilize, and distribute goods and services included in its discussion. Although Allah is the ultimate goal, the Islamic view of sharia economics and economic balance aims to create a decent and prosperous life for humanity. Islamic economics makes Allah its ultimate goal as well as its starting point.